Community readiness towards solid waste separation at source in Serdang, Selangor, Malaysia - Fadhilludin, Nurul Fadila (2015)
Malaysia especially Selangor is facing the increase of solid waste generation. Thus, source separation at source is seeing as a great opportunity to counter this problem. In implementing this program, it is essential to assess the community readiness level to ensure it’s successful. Hence the main objective of this study is to to study the community readiness towards solid waste separation at source in Taman Sri Serdang. The study will assess the leader opinion on his community readiness using Community Readiness Model;determine the community readiness towards this issue using questionnaire form; and propose a modified conceptual model for the community. The results show that leader of community in Taman Sri Serdang is in Preparation stage where he begin planning in earnest and community offers modest support of efforts. Using a set of questionnaire, six areas is being assessed; community efforts on solid waste separation at source, community knowledge in solid waste separation at source, community perception towards solid waste separation at source, community perception on leadership roles, awareness of available resources and community knowledge towards environment activity in their residential area. The results show that only half of the respondents are making an effort to separate their solid waste. Their knowledge in the issue is average and in their perception, solid waste separation at source activity is important. Their perception is solid waste is not an issue for the leader though some of them do recognize the efforts by the leader. Most of the community is also not aware on resources available for them. In addition, the community awareness on the environmental efforts and activities in their area is low. Thus, modified model is focusing on the community practice, attitude, knowledge sharing, law enforcement and incentives.